PANRETINAL PHOTOCOAGULATION PLUS INTRAVITREAL BEVACIZUMAB VERSUS PANRETINAL PHOTOCOAGULATION ALONE FOR PROLIFERATIVE DIABETIC RETINOPATHY - RIAZ , S; AHMED, N; KHAN, A; JABRAN, A; RAZA, I; AFZAL, T (Biological and Clinical Sciences Research Journal, 2024)
Proliferative diabetic retinopathy (PDR) is a severe and advanced stage of diabetic retinopathy, a major microvascular complication of diabetes mellitus. Objective: The basic aim of the study is to compare the panretinal photocoagulation plus intravitreal bevacizumab versus panretinal photocoagulation alone for proliferative diabetic retinopathy. Methodology: This randomized control trial was conducted at various tertiary care hospitals of Lahore and Rawalpindi from September 2023 to August 2024. Data include 40 patients, 80 eyes according to the study's criteria. Participants were randomly assigned into two equal groups using a computer-generated sequence. The first group, consisting of 20 patients, received PRP treatment alone and served as the control group. The second group, also consisting of 20 patients, received PRP combined with a single intravitreal injection of bevacizumab, forming the intervention group. Results: Both groups had a mean age of 54 ± 8 years and a male-to-female ratio of 3:2. Baseline best-corrected visual acuity (BCVA) was similar, with 0.4 ± 0.1 logMAR in the PRP group and 0.42 ± 0.1 logMAR in the combination group (p > 0.05). Central macular thickness (CMT) at baseline also showed no significant difference, with 310 ± 25 µm in the PRP group and 312 ± 27 µm in the combination group (p > 0.05), indicating well-matched groups for the study. Improvement in BCVA was significantly higher in the combination group (0.10 ± 0.03 logMAR) than in the PRP group (0.04 ± 0.02 logMAR, p = 0.02). Similarly, the reduction in central macular thickness (CMT) was more pronounced in the combination group (-22 ± 4 µm) compared to the PRP group (-5 ± 3 µm, p = 0.01). Conclusion: It is concluded that the combination of panretinal photocoagulation and intravitreal bevacizumab offers superior outcomes in managing proliferative diabetic retinopathy compared to PRP alone.